Taxonomic reintroduction of the holarctic saprotrophic fungus Crepidotus cinnamomeus - Soňa Jančovičová; Katarína Adamčíková; Miroslav Caboň; Mary G. Graddy; P. Brandon Matheny; Chance R. Noffsinger; Tim B. Wheeler; Slavomír Adamčík (Mycological Progress, 2024)
Crepidotus is a genus of common saprotrophic fungi well known especially in the Northern Hemisphere, but distribution patterns of individual species are not sufficiently understood. We redefined a taxonomic circumscription of Crepidotus cinnamomeus based on morphological and molecular congruencies between the type material and recent collections. The species is well delimited from other similar and currently accepted species of the genus. Crepidotus cinnamomeus was found to have a broad holarctic distribution with occurrences in North America, Europe and Asia where it grows on twigs and branches of deciduous trees and shrubs in preferably cold humid habitats. Here we present the first multilocus phylogeny of the genus, including portions of the RPB2 gene. Our study highlights the importance of sufficient sampling from broader areas supported by sequence data, which is essential for estimation of species delimitation, distribution and correct name assignment for Crepidotus species.